Fishing group catch sharing system: An Islamic perspective - Tasya Maulida; Yusrizal Yusrizal; Rahmi Syahriza (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2026)
This research aims to analyze the practice of the profit-sharing system between boat owners and fishermen in Paluh Sibaji Village, Pantai Labu Subdistrict, from the perspective of Islamic economics. Data were collected through direct observation in the field, in-depth interviews with ship owners and crew members, and documentation. The results show that this practice is in line with the mudharabah contract in Islamic economics, where the ship owner acts as shahibul maal and the fishermen as mudharib. Key values such as justice, willingness (ridha), and deliberation have been applied in the profit-sharing process. However, the absence of a written contract may lead to conflict or uncertainty regarding the rights and obligations of the parties, especially in emergencies or work accidents. Therefore, written records are highly recommended as a form of rights protection and transparency, by the principles of maqashid sharia, especially in the aspects of protecting property (hifzh al-mal) and soul (hifzh al-nafs). Public Interest Statement: This research examines the fish catch sharing system between boat owners and fishermen in Paluh Sibaji Village, Pantai Labu Sub-district, highlighting its importance for coastal communities. Through the analysis of traditional, oral practices, it emphasizes the need for fairness, transparency, and the protection of fishermen's rights. The findings reveal the local economic dynamics and advocate for written documentation to prevent conflicts and enhance fishermen's welfare. Ultimately, this study aims to inform better fisheries policies and support just and sustainable Islamic economic principles. Note: Early View Version